The heat shock protein 20 gene editing suppresses mycelial growth of Botryosphaeria dothidea and decreases its pathogenicity to postharvest apple fruits - Huang, Yonghong; Liu, Junping; Li, Jinghui; Sun, Meng; Duan, Yanxin (Frontiers in Microbiology, 2022)
Apple ring rot caused by Botryosphaeria dothidea is an essential and prevalent disease in the apple orchard in China. Our previous study demonstrated that dimethyl trisulfide (DT) from Chinese leek (Allium tuberosum) significantly suppressed the mycelial growth of B. dothidea, and inhibited the incidence of apple ring rot at postharvest. However, the mechanism underlying the inhibitory role of DT against B. dothidea is not fully understood. Comparing the control and the DT-treated B. dothidea mycelia transcriptomes revealed that a heat shock protein 20 (Hsp20) strongly responded to DT treatment. This study identified four Hsp20 genes throughout the B. dothidea genome (BdHsp20_1-4). Each BdHsp20 had an ACD conserved domain with a variable N-terminal region and a short C-terminal extension. The segmental duplication event has contributed to the expansion of the BdHsp20 gene family. Compared to the wildtype strain, the CRISPR/Cas9-edited BdHsp20 mutant (ΔBdHsp20) decreased the mycelial growth by 55.95% and reduced the disease symptom on postharvest apple fruit by 96.34%. However, the BdHsp20 complemented strain (ΔBdHsp20_C) significantly restored the growth and pathogenicity, which suggested that the BdHsp20 gene was closely involved in the growth and pathogenicity of B. dothidea. This study would accelerate the exploration of the molecular mechanism of the inhibitory effect of DT against B. dothidea and also provide new insights for the management of apple ring rot disease.